Privatization of water services in Metro Manila has it led to improved equity and better health? (2011)
This issue discusses the importance of water, primarily to the health of the people. It also highlights that like other natural resources, water resources in the country are dwindling because of pollution, indiscriminate use, and partly because of the El Nino phenomenon. In addition, it touches on the actions taken by the government in its pursuit to answer the Philippines` water problems.
Keywords: Privatization -- Rural water supply; Metropolitan Waterworks and Sewerage System